Compatibility of transformer construction materials with mineral, natural ester, and synthetic ester insulating oils - Sutan Chairul, Imran; Hidayah Rahim, Nor; Ab Ghani, Sharin; Shahril Ahmad Khiar, Mohd; Syahrani Johal, Muhammad; Nazri Mohamad Din, Mohamad (Bulletin of Electrical Engineering and Informatics, 2025)
This paper presents the experimental findings on the compatibility of kraft paper strips and gasket materials (fluoroelastomer (FE) and nitrile butadiene rubber (NBR)) with mineral (MO), natural ester (NE), and synthetic ester (SE) insulating oils. First, three insulating oil samples were prepared, and kraft paper strips, pressboards, and FE and NBR gasket materials were immersed in the oils. Metal catalysts were added into the insulating oil samples to simulate the actual conditions of oil-immersed transformers. The samples were thermally aged at 130 °C for 400 h. The results show that the tensile strength of the kraft paper immersed in NE increased by 1.82%, while the tensile strength of the kraft paper immersed in MO and SE decreased by 6.23 and 0.80%, respectively. The Shore A hardness of FE thermally aged in MO and SE decreased by 2.64 and 11.16%, respectively. In contrast, the FE thermally aged in NE became slightly harder, with a percentage degradation of +1.62%. On the other hand, the NBR thermally aged in MO, NE, and SE drastically decreased by 94.30, 86.70, and 93.67%, respectively. Hence, it is concluded that NBR is incompatible with the insulating oils tested in this study. In contrast, FE is most compatible with NE, followed by MO and SE.